Matrix analytic methods for evaluating loss performance in an atm networks - Abbas, Mazlan; Ahmad, Zainal Abidin (Penerbit UTM Press, 1992)
This paper will describe an analytical approach to the solutions of queueing models with finites capacity. The methods is chosen because its abilitiy to model exactly complex non-Markovian model which have correlated, non-renewal input process which is nearly impossible to get exact expressions by using classical methods of generating functions. We applied this methodology to compute the loss performance a of a queueing item specifically in the scenario of Asynchronous Transfer Mode (ATM) networks.